56.9k views
4 votes
Simplify: (−2a^2b)(4a^5b^2) need this quick thanks <3

User Mickers
by
5.7k points

2 Answers

2 votes

Assignment:
\bold{Simplify \ Equation: \ \left(-2a^2b\right)\left(4a^5b^2\right)}

<><><><><>

Answer:
\bold{-8a^7b^3}

<><><><><>

Explanation:
\downarrow\downarrow\downarrow

<><><><><>

[ Step One ] Remove Parenthesis (a) = a


\bold{-2a^2b\cdot \:4a^5b^2}

[ Step Two ] Multiply Numbers:
\bold{2\cdot \:4=8}


\bold{-8a^5a^2b^2b}

[ Step Three ] Apply Exponent Rules

Note:
\bold{Exponent \ Rules: \ a^b\cdot \:a^c=a^(b+c)}


\bold{a^5a^2=\:a^(2+5)=\:a^7}

<><><><><>


\bold{-8a^7b^2b}

[ Step Four ] Apply Exponent Rule

Note:
\bold{b^2b=\:b^(1+2)=\:b^3}


\bold{-8a^7b^3}

<><><><><><><>


\bold{\rightarrow Mordancy \leftarrow}

User Rafael Zeffa
by
5.4k points
5 votes

Answer:

See the attached figure for solution

Simplify: (−2a^2b)(4a^5b^2) need this quick thanks <3-example-1
User Yadhu Babu
by
5.2k points